Hubungan antara Gaya Belajar dengan Hasil Belajar Pendidikan Agama Islam di SMP Negeri 2 Kotanopan - Resky Nabila Batubara; Syamsiah Depalina Siregar (PT. Willy Print Art, 2025)
This study aims to determine the relationship between learning styles and student learning outcomes in Islamic Religious Education subjects at SMP Negeri 2 Kotanopan. The method used in this study is a descriptive method with a quantitative approach. The research sample was 30 grade VII students who were randomly selected using a simple random sampling technique. The research instrument was a questionnaire to measure students' learning styles and an Islamic Religious Education learning outcome test. Based on the results of data analysis, a correlation coefficient of 0.791 was obtained, indicating a positive and significant relationship between learning styles and learning outcomes. This means that the better the student's learning style, the higher the learning outcomes obtained in the Islamic Religious Education subjec. This study suggests that teachers better understand and pay attention to differences in student learning styles and apply appropriate learning methods so that learning outcomes can be improved. Students are also advised to recognize their respective learning styles so that they can optimize their learning process.